Theory of Natural Oscillatory Systems and Advance in Nanoelectronics - Грицунов, А. В.; Бондаренко, И. Н.; Пащенко, А. Г.; Бабиченко, О. Ю. (My University, 2018)
Specific treatments of some quantum phenomena substantial for progress in nanotechnology and nanoelectronics are presented. De Broglie waves are interpreted as oscillations of the generalized coordinates of natural oscillatory systems with distributed parameters (NOSs). The spatio-temporal localization of the NOS wave packets and Heisenberg’s uncertainty principle both are assumed to be results of the stochastic exchange with action quanta between different NOSs. The quantum kinematics (spatio-temporal evolution of NOS wave packets), quantum dynamics (interaction by means of random exchange with momentum-energy quanta between wave packets of different NOSs), and quantum statistics (probability laws for the stochastic exchange with action quanta between the wave packets in the Minkowski spacetime) are discussed. Both the action four-scalar and the momentum-energy four-vector, as the directional flow of action through 3D world, are assimilated with the geometry of NOS eigenmodes in the Minkowski spacetime. The conservation law for the action is supposed as a necessary condition for the energy-momentum conservation. The simplest examples of NOS wave packets are given. Some outcomes of application of this theory to solid-state phenomena are discussed.
Keywords: nanotechnology; matter wave; distributed oscillatory system; second quantization; action